Adolescent coping strategies in dealing with psychosocial impacts during the COVID-19 pandemic: A systematic review - Syamsiah, Resti Ikhda; Liana, Liana; Kusumawati, Mira Wahyu (Promotion and Prevention in Mental Health Journal, 2021)
The COVID-19 pandemic impacts the mental health of adolescents who are classified as vulnerable groups. Adolescents face various stressors, so they need coping strategies. Previous research has discussed psychosocial problems in adolescents due to the pandemic but is still limited to discussing how adolescents deal with stress during the pandemic. This systematic review aims to identify the psychosocial impacts and coping strategies of adolescents during the pandemic. This systematic review research uses various sources of information from journal articles. The databases used are ScienceDirect, ProQuest, and Ebsco. The instrument used is the PRISMA checklist. Based on results of literature research from 3 databases, according to predetermined keywords, 370 scientific articles were obtained. According to the inclusion criteria, further analysis was carried out, and 15 full texts were obtained for review. The psychosocial impacts experienced by adolescents during the pandemic are classified into two: psychological impacts and social impacts. Psychological impacts include depression, anxiety, stress, worry, sadness, PTSD, anxiety, helplessness, fear, and psychological stress. Social impacts consist of loneliness, feelings of isolation, social withdrawal or restriction, and lack of family support. Adolescent coping abilities during the COVID-19 pandemic are classified into positive and negative coping. Adolescents use coping to deal with psychosocial problems during the pandemic, classified into positive (active) and negative (passive) coping. Positive coping can improve adolescent mental health, while negative coping is at risk for psychosocial problems in adolescents.